The Relationship Between Breastfeeding Mother Diet and The Frequency of Exclusive Breastfeeding in Infants - Panjaitan, Raini; Windi Suastiani; Sari Desi Esta Ulina Sitepu; Bertalina Tarigan; Helida Handayani S; Selamat Tuahta Sipayung (JURNAL KESMAS DAN GIZI (JKG), 2025)
The maternal diet during breastfeeding was related to breast milk production and indirectly affected the nutritional status of infants. During the breastfeeding period, maternal nutritional needs increased, making it important to maintain a balanced food intake. The amount and type of food consumed influenced the volume and quality of breast milk. This study aimed to analyze the relationship between maternal diet and the frequency of exclusive breastfeeding in infants in the Pegajahan Health Center work area. The method used was quantitative research with a cross-sectional study approach. The population in this study consisted of 165 mothers who had babies aged 0-6 months, with a sample of 61 mothers selected through purposive sampling techniques. The independent variable in this study was the diet of breastfeeding mothers, while the dependent variable was the frequency of exclusive breastfeeding. Data collection was carried out through interviews and questionnaires, with hypothesis analysis using the chi-square statistical test. The results showed that the majority of mothers were in the age range of 20-30 years (65.57%), had a final education in high school (42.62%), and most of them worked (81.96%). Most mothers had a diet classified as frequent (77.04%), and the frequency of breastfeeding was more than eight times a day (78.68%). Bivariate analysis showed a significant relationship between maternal diet and the frequency of exclusive breastfeeding, with a p-value = 0.000. This study concluded that there was a significant relationship between maternal diet and the frequency of exclusive breastfeeding in mothers at the Pegajahan Health Center, Serdang Bedagai Regency. Consistent efforts by healthcare professionals are essential in delivering nutritional counseling to breastfeeding mothers.